2021
DOI: 10.1210/clinem/dgab545
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Improved Classification of Type 2 Diabetes: Lessons From Research into the Heterogeneity of a Complex Disease

Abstract: Context Accumulating evidence indicates “type 2 diabetes (T2D)” is phenotypically heterogeneous. Defining and classifying variant forms of T2D are priorities to better understand its pathophysiology and usher clinical practice into an era of “precision diabetes”. Evidence Acquisition and Methods We reviewed literature related to heterogeneity of T2D over the past five decades and identified a range of phenotypic variants of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 119 publications
2
14
0
Order By: Relevance
“…• The five diabetes subgroups were developed using data from European cohorts [6] but diabetes phenotypes and drug responses can differ between ethnic groups [59,65,66]. Replication studies in non-White people with diabetes identified additional subgroups but were often based on different sets of clustering variables and/or diabetes durations [27,29,30,36,[38][39][40][41].…”
Section: Methodological Aspects and Open Questionsmentioning
confidence: 99%
“…• The five diabetes subgroups were developed using data from European cohorts [6] but diabetes phenotypes and drug responses can differ between ethnic groups [59,65,66]. Replication studies in non-White people with diabetes identified additional subgroups but were often based on different sets of clustering variables and/or diabetes durations [27,29,30,36,[38][39][40][41].…”
Section: Methodological Aspects and Open Questionsmentioning
confidence: 99%
“…The atypical group also had a significantly higher T2D gePS than the ML T1D groups, and their T1D rsPS fell between those of the individuals with ML T1D and T2D ( Table 3 , Fig 3 , S1 Fig ). These genetic results suggest that the individuals with AD identified by these algorithms may have biologic differences as compared to patients with typical forms of diabetes, building upon the idea that forms of diabetes lie on a spectrum, and some individuals with AD may reside somewhere between “typical” T1D and “typical” T2D, or may have features characteristic of multiple forms of diabetes [ 23 ]. Regarding the non-significantly higher gePS for T2D among AD cases as compared to those with ML, this finding may be related simply to chance or may signify that individuals who develop diabetes even at lower BMI may have elevated risk for diabetes due to alternate pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Adding to the confusion, monogenic forms of diabetes, including neonatal and maturity-onset diabetes of the young (MODY), are relatively rare causes of pediatric-onset diabetes [4] that may resemble T1D or T2D but require genetic testing for diagnosis. Atypical forms of diabetes or atypical presentations of common forms of diabetes are more frequent in non-European individuals [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is heightened interest in the challenges surrounding diagnosis of diabetes type [5,[10][11][12][13][14][15][16][17][18], the prevalence of imprecise diagnosis of pediatric diabetes types and the factors associated with imprecise diagnosis are not fully understood. Therefore, we aimed to study imprecise diagnosis of diabetes type in racially and ethnically diverse youth.…”
Section: Introductionmentioning
confidence: 99%